2013
DOI: 10.1155/2013/746749
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Endothelial Growth Factor Receptor-1 Expression in Breast Cancer and Its Correlation to Vascular Endothelial Growth Factor A

Abstract: VEGF-A is the most potent angiogenic factor in tumour angiogenesis. Its effects are mediated via two receptors VEGFR-1 and VEGFR-2. Primary aim of our study was to examine the expression of VEGFR-1 in breast cancer and its correlation to VEGF expression, lymph node status, tumour size, histological grade, and hormone receptor status. To examine the VEGFR-1 and VEGF expressions in tumour and surrounding tissue of 51 breast cancer patients, and in healthy breast tissue of 30 benign breast diseases patients, we u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
26
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 27 publications
5
26
1
Order By: Relevance
“…In our study we demonstrated a weak correlation between the histological grade and the VEGF expression which was not significant (p-0.06). This finding was in accordance with the results of others similar (8,10,11,14) . On the other hand Linderholm B et al (4) reported a significant correlation between VEGF expression and grading of breast carcinoma while Ghasemi M et al (13) showed inverse correlation.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…In our study we demonstrated a weak correlation between the histological grade and the VEGF expression which was not significant (p-0.06). This finding was in accordance with the results of others similar (8,10,11,14) . On the other hand Linderholm B et al (4) reported a significant correlation between VEGF expression and grading of breast carcinoma while Ghasemi M et al (13) showed inverse correlation.…”
Section: Discussionsupporting
confidence: 94%
“…In our study we found 93.33% of cases showing positivity for VEGF expression. Similar results were seen in some of the previous studies (10,11,12,13) . High number of positive cases for VEGF sustains the concept that this growth factor is involved in the development of breast tumors by different mechanism (10) .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…VEGF-C expression is associated with poor prognosis for these patients, including patients with stage I NSCLC [29]. VEGFR-1 and VEGF expressions were significantly increased in breast cancer in relation to surrounding tissue and the VEGF expression was significantly increased in lymph node positive breast cancer patients [30]. VEGF could impact ovarian cancer's malignant progression [31].…”
Section: Non-digestive Cancersmentioning
confidence: 99%